(3GdJejjR aj GdbQGAI hGdJQHjI GdhWfjI hGdJfTFI GdeOfjI aj GdeQMdI GdGHJOGFjI(B-(3ebGQHI Ydi CSGS GdfhY GdGLJeGYjs - (3cHGQI TYQGfj, CeGfjs; (3TQa GdOjf, agejIs ((3HjQhJs (3GddLfI GdCgdjI deJGHYI bVGjG GdeQCIs, 2006)
(3JQJcR gPg GdOQGSI Ydi ebGQHI JMdjdjI Ydi CSGS GdfhY GdGLJeGYj ddcJH GdeOQSjI aj GdeQMdI GdGHJOGFjI (B((3cJH GdbQGAI aj GddZI GdYQHjI hcJH GdJQHjI GdhWfjI hGdJfTFI GdeOfjI(B) (3hgj GdcJH GdJj JNGWH Ybhd GdJdGejP hbdhHge, agj aj JbOjegG ddbUU hGdMcGjGJ hGdeYdheGJ GdeJfGSHI eY CYeGQge heSJhjGJge JDKQ aj Jchjfge GdfaSj hGdYbdj hJDKQ HGdJGdj aj HfGA hYjge GdPGJj hGdehVhYj(B. (3hJcef CgejI gPg GdOQGSI aj chfgG GdOQGSI GdefgLjI GdChdi ddJYQa Ydi ecGfI GdJejjR aj gPg GdefGgL, hbO MOOJ CgOGa GdOQGSI aj CQHYI eSJhjGJ(B: 1( (3GdJYQa Ydi GdeMJhi GdLfOQj deLehYI GdcJH ehVhY GdOQGSI(B. 2) (3GdJYQa Ydi GdUhQ GdfeWjI GdJj JbOegG gPg GdcJH hGdQSGFd GdJj JHKgG YHQ gPg GdUhQ(B. 3) (3eQGbHI GddZI GdeSJNOeI aj GdcJH hJMdjdgG Ydi CSGS GdfhY GdGLJeGYj(B. 4) (3UjGZI JhUjGJ hebJQMGJ YedjI JSge aj JWhjQ GdefGgL HGJLGg GdeSGhGI GdeWdhHI Hjf GdLfSjf(B. (3CeG YjfI GdOQGSI agj GdcJH GdUGOQI Yf GdeQcR GdJQHhj ddHMhK hGdEfeGA (B(6 (3cJH aj GddZI GdYQHjI h(B6 (3aj JeGQjf GddZI GdYQHjI h(B6 (3aj GdJQHjI GdhWfjI hGdeOfjI h(B3 (3aj JeGQjf JWHjbGJ GdJQHjI GdhWfjI(B). (3hbO Je JMdjd GdCOhGQ GdLfOQjI GdhGQOI aj GdcJH GdeOQSjI hGdUhQI GdYGeI ddPchQ hGdEfGK, hGdUhQ hGdQShe dQUO GdCOhGQ hJMdjd GddZI GdeSJNOeI hGdJhbYGJ hGdJUhQGJ GdeHfjI Ydi GdCOhGQ GdJj Je QUOgG(B. (3hbO JHjf HbGA GdJejjR GdLfOQj GdhGVM deUdMI GdPchQ aj GdCOhGQ hGddZI hGdJhbYGJ hGdUhQ GdehLhOI aj YjfI GdcJH GdeOQSjI ddeQMdI GdGHJOGFjI(B. (3hCKHJJ GdOQGSI GdJhGLO GdeMOhO dCOhGQ CfKhjI eJfhYI ceG CXgQJ bUhQkG aj eNGWHI GdaJjGJ cCaQGO eJSGhjf(B.s
(3GdfhY (B: (3cJGHs
Keywords: (3GdLfOQs; Cycle primaire; Elementary Education; Gender; Livres Scolaires; Sexe; Textbooks; (3GdcJGH GdeOQSjs; (3GdeQMdI GdGHJOGFjIs